Pemikiran Sufistik dan Toleransi Beragama KH. Sholeh Bahruddin di Pesantren Ngalah Pasuruan - Nafis, Muhammad Muntahibun; Najib, Muhammad Ainun (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2017)
Sufism and tarekat (Sufi order) play a significant role in building and enhancing mutual-peaceful dialogue between Islam and other religions and cultures. The Sufis establish cooperation with followers of other religions. This is because Sufism holds moderate view and understanding of Islamic doctrines. Sufism is, therefore, not limited only on spirituality and mystical realm, but it is also able to create a harmonious relationship among humans and between humans and nature. This article seeks to present a related study on the doctrine of religious tolerance within Sufism promulgated by KH. Sholeh Bahruddin, the headmaster of Pesantren (Islamic boarding school) Ngalah Pasuruan East Java. Kiai Sholeh sees Sufism as the main foundation of religious tolerance. As the murshid of the Tarekat Q?dir?yah wa Naqsaband?yah Mujaddad?yah Kh?lid?yah Kiai Sholeh has intensively cultivated Islam ra?mah li al-??lam?n in the pesantren he leads. This doctrine emphasizes that Islam ra?mah li al-??lam?n perceives all human beings as kabeh dulur (all are brothers) regardless of their religious and social background, and political preference. Through the concept of kabeh dulur, Kiai Sholeh builds human relationships with anyone, including people of different faiths and beliefs.